Comparison of two different operational models for complex terrain in neutral flow. (1st January 2001) - Wroblewski, A.; Coppalle, A.; Guillermo, R.
The estimation of pollutant concentration from sources in complex terrain is something very difficult to achieve in an operational situation. In this paper, we evaluate two different approaches of wind-field modelling. The first is a fully used, mass consistent, model (MINERVE) from Aria Technologies, based on the interpolation of wind data under the constraint of minimising flux divergence. The second is a simplified approach based on the resolution of dynamic flow on the surface, in accordance with an estimation of the free wind field (AIRVIRO) from SMHI. The models are tested against two-dimensional hills according to the Finardi et al. (1992) experiments. The wind profiles obtained with the two models have been compared with the data from wind tunnel experiments.